Analyzing the Impact of Spotify and Wordwall.net on Vocabulary Acquisition: A Study of non-English major Students' Preferences - Mallisa, Intan Clara Briliant; Mbato, Concilianus Laos (VELES Voices of English Language Education Society, 2023)
This research explores the impact of digital platforms, specifically Spotify and wordwall.net, on vocabulary acquisition among students in primary school teacher education (PGSD). The study employs qualitative methodologies, including focus group discussions, to gauge student preferences and the effectiveness of these platforms in enhancing second language vocabulary learning. The research participants consist of prospective PGSD students who engage with both platforms, offering insights into their experiences and preferences. The findings reveal a strong preference for Spotify, with 75% of participants favoring its use for language learning. Spotify's appeal lies in its immersive and contextual approach, leveraging music as a medium for vocabulary learning. This preference underscores the platform's ability to integrate language learning into daily routines, making it more engaging and accessible. wordwall.net, preferred by 25% of participants, is recognized for its interactive and game-based approach, offering a dynamic and enjoyable method for vocabulary acquisition. The study highlights the increasing relevance of digital tools in language education, reflecting a shift towards innovative, technology-driven learning methods. It suggests that integrating platforms like Spotify and wordwall.net can cater to diverse learning styles, making vocabulary learning more engaging, effective, and aligned with the digital habits of contemporary learners. The research contributes to the understanding of how digital platforms can enhance language learning and offers insights for educators in adapting their teaching methods to include these tools effectively.